Procesos departamentales e indicadores de desempeño en organizaciones del servicio público - Andrade Santos, Alexandra Liliana (2022)
This research analyzes the importance of departmental processes and performance indicators in organizations, since it is important to apply processes in the different departments that make up the company to establish strategies that reduce the presence of work overload, duplication of tasks, errors and Confusions related to the lack of knowledge of the activities, as well as the processes necessary for each of the tasks and functions of the positions. The objective of the research was to analyze the departmental processes and performance indicators in the Provincial Directorate of Irrigation and Drainage. The methodology used was a mixed approach, non-experimental and crosssectional design, descriptive research, field, the technique was observation, survey and interview, the sample was intentional in 35 officials. The results showed that the management does not have a work planning, process manual, performance indicators, graphic representation and symbology of the processes, the staff does not have a cooperative or communicative attitude with their colleagues, nor do they evaluate the results. In turn, they do not have well defined responsibilities, activities and processes, thus causing the objectives set not to be achieved, the activities are repeated and they cannot respond to the needs of the users. Therefore, they consider it necessary to create work teams and implement a process map.